2006
DOI: 10.1007/s00441-005-0128-6
|View full text |Cite
|
Sign up to set email alerts
|

Prion protein expression in bovine podocytes and extraglomerular mesangial cells

Abstract: The cellular form of the prion protein (PrP(c)) is thought to be a substrate for an abnormal isoform of the prion protein (PrP(sc)). One emerging hypothesis is that the proposed conversion phenomenon takes place at the site at which the infectious agent meets PrP(c). PrP(c) is abundant in the central nervous system, but little is known about the cell-type-specific distribution of PrP(c) in non-neuronal tissues of cattle. We have studied whether PrP(c), a protein found predominantly in neurons, also exists in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 75 publications
1
6
0
Order By: Relevance
“…This finding is in accordance with the reactivity of a rabbit antiserum raised against a slightly larger sequence (VEQMCITQYQRESQAY-YQR) of bovine PrP that also exhibited no isoform specificity (Takahashi et al 1999). Furthermore, applicability of this sandwich ELISA has been demonstrated in a previous study on cell-type-specific expression of PrP c in bovine kidney samples (Amselgruber et al 2006). Compared with the latter study, ELISA signals for mammary glands were relatively weak and indicated that for PrP c in this tissue the extraction efficacy of the applied method was low.…”
Section: Resultssupporting
confidence: 87%
“…This finding is in accordance with the reactivity of a rabbit antiserum raised against a slightly larger sequence (VEQMCITQYQRESQAY-YQR) of bovine PrP that also exhibited no isoform specificity (Takahashi et al 1999). Furthermore, applicability of this sandwich ELISA has been demonstrated in a previous study on cell-type-specific expression of PrP c in bovine kidney samples (Amselgruber et al 2006). Compared with the latter study, ELISA signals for mammary glands were relatively weak and indicated that for PrP c in this tissue the extraction efficacy of the applied method was low.…”
Section: Resultssupporting
confidence: 87%
“…These observations confirm and extend the results of a previous report that indicated the presence of PrP C in bovine glomeruli. 39 Scrapie-infected hamsters and CJD patients have been shown to excrete PrP Sc in urine and PrP Sc has been detected in the collecting tubules of scrapieinfected hamsters that shed PrP Sc in urine. 40 While in principle the presence of PrP C in the bovine kidney may render it susceptible to prion infection, PrP Sc has not been detected in the urine of BSE-infected cattle 21 and to our knowledge, kidneys from BSE-infected cattle have not been evaluated for the presence of PrP Sc or BSE infectivity.…”
Section: Discussionmentioning
confidence: 99%
“…Filtration of PrP d at the glomeruli would result in its presence in the urinary system and therefore explain its detection—and that of infectivity—in the urine 32. Such protein filtration could be enhanced following injury to podocytes, in which PrP c has been described 33, and disruption of the slit diaphragm, which would result in proteinuria as well as prionuria. Some of the PrP d filtered at the glomerular level could be reabsorbed at the bend of Henle's loops, where the osmotic pressure of the urine is at its highest, leading to accumulation in the papillary interstitium directly from the point of release or after amplification in infected fibroblasts.…”
Section: Discussionmentioning
confidence: 99%